Τhe observational and empirical thermospheric CO2 and NO power do not exhibit power-law behavior; an indication of their reliability. (March 2018) - Varotsos, C.A.; Efstathiou, M.N.
Abstract: In this paper we investigate the evolution of the energy emitted by CO2 and NO from the Earth's thermosphere on a global scale using both observational and empirically derived data. In the beginning, we analyze the daily power observations of CO2 and NO received from the Sounding of the Atmosphere using Broadband Emission Radiometry (SABER) equipment on the NASA Thermosphere-Ionosphere-Mesosphere Energetics and Dynamics (TIMED) satellite for the entire period 2002–2016. We then perform the same analysis on the empirical daily power emitted by CO2 and NO that were derived recently from the infrared energy budget of the thermosphere during 1947–2016. The tool used for the analysis of the observational and empirical datasets is the detrended fluctuation analysis, in order to investigate whether the power emitted by CO2 and by NO from the thermosphere exhibits power-law behavior. The results obtained from both observational and empirical data do not support the establishment of the power-law behavior. This conclusion reveals that the empirically derived data are characterized by the same intrinsic properties as those of the observational ones, thus enhancing the validity of their reliability. Highlights: The temporal evolution of the energy emitted by CO2 and NO from Earth's thermosphere on a global scale is explored. The detrended fluctuation analysis is used to study the scaling dynamics of the above-mentioned time series. The intrinsic properties of both observed (2002-2016) and empirical time series (1947-2016) are the same. The conclusion is that the empirically derived data are consistent with observations.